Biomass-based hard carbon material, preparation method thereof and battery
By performing specific treatment of biomass carbon sources and controlling the pore structure of their hard carbon materials, the problems of insufficient sodium storage capacity and cycle stability of biomass-based hard carbon materials in the prior art are solved, and higher sodium storage capacity and stability are achieved.
Patent Information
- Application Number
- CN202411947995.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The pore structure of existing biomass-based hard carbon materials is difficult to adjust, resulting in insufficient reversible sodium storage capacity and cycle stability.
By subjecting the biomass carbon source to alkali treatment, acid treatment, crystallization pretreatment and carbonization, the pore structure of the hard carbon material is coordinated to form a closed pore structure to improve sodium storage capacity.
The pore structure regulation of biomass-based hard carbon materials has been achieved, significantly improving its reversible sodium storage capacity and cycling stability.
Smart Images

Figure CN119735194A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of battery technology and relates to a biomass-based hard carbon material and a preparation method thereof and a battery, and in particular to a biomass-based hard carbon material more suitable for sodium ion batteries and a preparation method thereof and a sodium ion battery. Background Art
[0002] With the reduction of traditional fossil energy reserves and the environmental problems caused by mining and utilization, countries have stepped up their efforts in the research and development and utilization of new energy technologies, aiming to achieve energy structure transformation and upgrading and promote sustainable economic and social development. Lithium-ion battery energy storage technology has made great progress in energy storage density and technological maturity, and has been widely used in electric vehicles, large-scale energy storage and other fields. However, lithium-ion batteries have shortcomings such as low abundance of lithium resources in the earth's crust, uneven distribution, and high battery costs. In comparison, sodium-ion batteries have become a potential alternative to lithium-ion batteries due to their abundant resources and low costs. In recent years, their research and development have developed rapidly around the world, showing broad application prospects.
[0003] Negative electrode materials are one of the key materials for the development and application of sodium-ion battery technology. Among them, carbon materials, as the negative electrode of sodium-ion batteries, stand out for their excellent electrochemical performance, good stability and low cost; and biomass-based hard carbon has a unique non-layered structure, which can provide more sodium ion storage sites, showing a high sodium storage capacity and becoming one of the research hotspots of negative electrode materials for sodium-ion batteries. From the perspective of the sodium storage mechanism of hard carbon negative electrode, different types of pore structures in hard carbon materials have an important influence on the electrochemical performance of sodium-ion batteries. Among them, hard carbon materials with closed pore structures are more conducive to sodium storage. As the content of closed-pore structure increases, the sodium ion storage sites increase, and the specific surface area of hard carbon also decreases accordingly. This structural feature can significantly improve the low-voltage platform capacity, initial coulombic efficiency and cycle stability of hard carbon negative electrode.
[0004] At present, the mainstream preparation technology route of biomass-based hard carbon mainly includes raw material pretreatment, material purification, pre-carbonization, crushing, high-temperature carbonization and other related processes. It is difficult to adjust the pore structure of hard carbon materials in this route, so it is impossible to improve the reversible sodium storage capacity and cycle stability of hard carbon materials.
[0005] Therefore, how to adjust the pore structure of biomass-based hard carbon materials and improve their reversible sodium storage capacity and cyclic stability is a technical problem that needs to be solved urgently. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a biomass-based hard carbon material and a preparation method and a battery thereof. The preparation method provided by the present invention sequentially treats the biomass carbon source with alkali, acid, crystallization pretreatment and carbonization. The above preparation processes cooperate with each other to regulate the pore structure of the hard carbon material and form a closed-cell structure. This special closed-cell structure has a large pore volume, which improves the reversible sodium storage capacity and cycle stability of the bio-based hard carbon material.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a biomass-based hard carbon material, the preparation method comprising the following steps:
[0009] The biomass carbon source is sequentially subjected to alkali treatment, acid treatment, crystallization pretreatment and carbonization to obtain the biomass-based hard carbon material.
[0010] It should be noted that the biomass carbon source described in the present invention refers to a general term for all biological organisms produced by photosynthesis, including plants, crops, forest output waste, marine products (such as various seaweeds), etc. The present invention is applicable to all types of materials that can be known within a reasonable range by those skilled in the art; for example, it can be wheat straw, peanut shells, rapeseed stalks, rice husks, bamboo, coconut shells, corn stalks or larch, etc., which have abundant material sources and low costs.
[0011] The preparation method provided by the present invention coordinates various preparation processes and preparation sequences to regulate the raw material components of biomass carbon source, namely cellulose, hemicellulose and lignin, and the crystallinity of cellulose, thereby obtaining a biomass carbon source with high content and high crystallinity. The high-content crystalline cellulose can be converted into long graphite layers in the subsequent low-carbonization process, surrounding and shrinking the active sites to form a closed pore structure (i.e., a closed-pore structure), thereby achieving the regulation of the pore structure of the hard carbon material obtained by carbonization, and achieving the purpose of improving the reversible sodium storage capacity and cyclic stability of the biomass-based hard carbon material.
[0012] Biomass carbon sources include cellulose, hemicellulose and lignin, and the content of cellulose and hemicellulose is relatively high; excessively high content of amorphous hemicellulose and lignin components will hinder the movement of cellulose molecular chains during the subsequent low-temperature pretreatment process, thereby affecting the crystallization of cellulose; while excessively low content of amorphous hemicellulose and lignin components will cause excessive graphitization of the carbon layer during high-temperature carbonization, which is not conducive to the formation of nanopores; therefore, the alkali treatment and acid treatment in the present invention, on the one hand, play a role in removing impurities in the biomass carbon source, and on the other hand, during the alkali treatment process, the hemicellulose and lignin in the biomass carbon source are partially dissolved, thereby achieving the purpose of increasing the cellulose content in the biomass carbon source, and through the acid treatment, the raw material components of the biomass carbon source are further regulated. Cellulose, hemicellulose and lignin also play the role of neutralizing the alkaline substances in the alkali treatment process; after alkali treatment and acid treatment, the crystalline area in the biomass carbon source will swell and partially dissolve, thereby increasing the content of non-crystalline cellulose, and non-crystalline cellulose is not conducive to the formation of a closed pore structure. Then, through crystallization pretreatment, the glass transition temperature range of cellulose is controlled, so that the cellulose molecular segments move and rearrange, and the cellulose completes the transition from amorphous to crystalline, thereby increasing the crystallinity content of cellulose in the biomass carbon source; high-content crystalline cellulose contributes to the formation of closed pores in hard carbon after high-temperature carbonization, and the obtained closed-pore structure has a larger pore volume, thereby achieving the purpose of improving the reversible sodium storage capacity and cyclic stability of biomass-based hard carbon materials.
[0013] In the present invention, the preparation process and preparation sequence of alkali treatment, acid treatment, crystallization pretreatment and carbonization must be coordinated. Without any one of the steps, closed-cell adjustment cannot be achieved and a closed-cell structure with a larger pore volume cannot be obtained.
[0014] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0015] Preferably, the present invention first dries and crushes the biomass carbon source, controls the moisture content to 5% to 10%, such as 5%, 6%, 7%, 8%, 9% or 10%, and the particle size is 10 to 50 mesh, such as 10 mesh, 20 mesh, 30 mesh, 40 mesh or 50 mesh, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0016] Preferably, the alkali treatment comprises:
[0017] The biomass carbon source is mixed with an alkaline solution and subjected to an alkali treatment to obtain an alkali-treated product.
[0018] It should be noted that the alkaline substance in the alkaline solution of the present invention is a conventional technical solution, for example, including but not limited to at least one of ammonia water, potassium hydroxide or sodium hydroxide.
[0019] Preferably, the concentration of the alkaline solution is 0.1-5 mol / L, for example, 0.1 mol / L, 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L, 4 mol / L, 4.5 mol / L or 5 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] Preferably, the mass ratio of the biomass carbon source to the alkaline solution is 1:(5-10), for example 1:5, 1:5.5, 1:6, 1:6.5, 1:7, 1:7.5, 1:8, 1:8.5, 1:9, 1:9.5 or 1:10, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] In the present invention, the concentration of the alkaline solution is 0.1-5 mol / L and the mass ratio of the biomass carbon source to the alkaline solution is 1:(5-10). The synergistic effect can better remove impurities and dissolve part of hemicellulose and lignin, thereby increasing the cellulose content in the biomass carbon source; thereby better improving the performance of the material.
[0022] Preferably, the alkali treatment time is 1 to 4 hours, such as 1 hour, 2 hours, 3 hours or 4 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0023] Preferably, the acid treatment comprises:
[0024] The alkali-treated product is mixed with an acidic solution and subjected to acid treatment to obtain an acid-treated product.
[0025] It should be noted that the acidic substance in the acid solution of the present invention is a conventional technical solution, for example, including but not limited to at least one of hydrochloric acid, hydrofluoric acid or nitric acid; and after acid treatment, pure water washing, centrifugation, drying and other treatment processes can be carried out to obtain the acid-treated product.
[0026] Preferably, the concentration of the acidic solution is 0.1-5 mol / L, for example, 0.1 mol / L, 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L, 4 mol / L, 4.5 mol / L or 5 mol / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable. However, the concentration of the acidic solution is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0027] Preferably, the mass ratio of the biomass carbon source to the acidic solution is 1:(5-10), for example 1:5, 1:5.5, 1:6, 1:6.5, 1:7, 1:7.5, 1:8, 1:8.5, 1:9, 1:9.5 or 1:10, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] In the present invention, the concentration of the acidic solution is 0.1-5 mol / L, and the mass ratio of the biomass carbon source to the acidic solution is 1:(5-10), which is more conducive to the neutralization and impurity removal of the biomass after alkali washing.
[0029] Preferably, the acid treatment time is 1 to 4 hours, such as 1 hour, 2 hours, 3 hours or 4 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] Furthermore, the present invention regulates the time of alkali treatment to 1 to 4 hours and / or the time of acid treatment to 1 to 4 hours in order to remove impurities from the biomass carbon source and regulate the cellulose content.
[0031] Preferably, the crystallization pretreatment comprises:
[0032] The acid-treated product is subjected to low-temperature pretreatment.
[0033] Preferably, the heating rate of the low-temperature pretreatment is 1 to 3°C / min, for example, 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min or 3°C / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] Preferably, the insulation temperature after the low-temperature pretreatment is 100-180°C, for example, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C or 180°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] In the present invention, the insulation temperature of the low-temperature pretreatment is adjusted to 100-180°C, which is more conducive to controlling the glass transition temperature range of cellulose, so that the cellulose molecular segments move and rearrange, and the cellulose completes the transition from an amorphous state to a crystalline state, thereby increasing the crystallinity content of cellulose. In the subsequent carbonization process, it helps to form a closed pore structure, thereby improving the capacity and cycle performance.
[0036] Preferably, the holding time after the low-temperature pretreatment heating is 10 to 30 minutes, for example, 10 minutes, 15 minutes, 20 minutes, 25 minutes or 30 minutes, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] In the present invention, the holding time after the low-temperature pretreatment is preferably 10 to 30 minutes, which is conducive to the full creeping rearrangement of the cellulose molecular segments.
[0038] Preferably, the cooling rate during the cooling process after the low-temperature pretreatment and insulation is 15 to 20°C / min, for example, 15°C / min, 18°C / min, 19.5°C / min or 20°C / min, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] In the crystallization pretreatment process, the present invention does not adopt a natural cooling method to room temperature, but controls the cooling rate to achieve a regular cooling process from the insulation temperature to room temperature, which is more conducive to the structure of the cellulose molecular chain segments after rearrangement and crystallization without being destroyed; and the preferred cooling rate is 15-20°C / min, which helps to quickly freeze the molecular chain segments and maintain the integrity of the crystal structure.
[0040] Preferably, the carbonization includes sequentially performing pre-carbonization and high-temperature carbonization.
[0041] In the present invention, the purpose of pre-carbonization is to remove moisture, ash and volatile matter in the carbon source to form hard carbon with initial open pores distributed on the surface.
[0042] Preferably, the heating rate of the pre-carbonization is 15-20°C / min, such as 15°C / min, 18°C / min or 20°C / min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0043] Preferably, the holding temperature after the pre-carbonization heating is 450-600°C, such as 450°C, 500°C, 550°C or 600°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] Preferably, the holding time after the pre-carbonization heating is 2 to 5 hours, such as 2 hours, 3 hours, 4 hours or 5 hours, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0045] Preferably, the pre-carbonized material is crushed to obtain a product with a median particle size D50 of 5 to 10 μm, such as 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] Preferably, the heating rate of the high temperature carbonization is 3-5°C / min, such as 3°C / min, 4°C / min or 5°C / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] Preferably, the insulation temperature after the high-temperature carbonization heating is 1000-1500°C, for example, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C or 1500°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] Preferably, the heat preservation time after the high-temperature carbonization heating is 3 to 5 hours, such as 3 hours, 4 hours or 5 hours, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] Preferably, the atmosphere in the carbonization process of the present invention is a protective atmosphere, which includes a nitrogen atmosphere and / or an inert gas atmosphere, etc. The inert gas includes but is not limited to argon or helium.
[0050] As a preferred technical solution, the preparation method comprises the following steps:
[0051] Mixing a biomass carbon source with an alkaline solution having a concentration of 0.1 to 5 mol / L, and subjecting the mixture to an alkali treatment for 1 to 4 hours to obtain an alkali-treated product;
[0052] The alkali-treated product is mixed with an acidic solution having a concentration of 0.1 to 5 mol / L, and subjected to acid treatment for 1 to 4 hours to obtain an acid-treated product;
[0053] The product after the acid treatment is subjected to a crystallization pretreatment, the crystallization pretreatment comprising: heating to 100-180°C at a heating rate of 1-3°C / min, maintaining the temperature for 10-30min, and then cooling at a cooling rate of 15-20°C / min to obtain a substance after the crystallization pretreatment;
[0054] Pre-carbonizing the pre-crystallized material at 450-600° C., crushing the pre-carbonized material, and carbonizing the crushed product at a high temperature of 1000-1500° C. to obtain the biomass-based hard carbon material;
[0055] Wherein, the mass ratio of the biomass carbon source to the alkaline solution is 1:(5-10), and the mass ratio of the biomass carbon source to the acidic solution is 1:(5-10).
[0056] In a second aspect, the present invention provides a biomass-based hard carbon material, wherein the biomass-based hard carbon material is prepared by the preparation method described in the first aspect;
[0057] The biomass-based hard carbon material has a closed-pore structure inside.
[0058] The hard carbon material provided by the present invention has a closed-pore structure inside, which is more conducive to sodium storage. As the content of the closed-pore structure increases, the number of sodium ion storage sites increases. This structural characteristic can significantly improve the capacity and cycle stability of the hard carbon negative electrode.
[0059] Preferably, the pore volume of the closed-cell structure is 1.4 to 2.0 cm 3 / g, for example 1.4cm 3 / g, 1.5cm 3 / g, 1.6cm 3 / g, 1.7cm 3 / g, 1.8cm 3 / g, 1.81cm 3 / g, 1.82cm 3 / g, 1.83cm 3 / g, 1.84cm 3 / g, 1.85cm 3 / g, 1.86cm 3 / g, 1.87cm 3 / g, 1.88cm 3 / g, 1.89cm 3 / g, 1.9cm 3 / g, 1.93cm 3 / g, 1.95cm 3 / g, 1.98cm 3 / g or 2.0cm 3 / g, etc., preferably 1.8 to 2.0 cm 3 / g, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0060] The closed-cell structure of the present invention has a larger pore volume and is more conducive to sodium storage.
[0061] In a third aspect, the present invention further provides a battery, comprising the biomass-based hard carbon material as described in the second aspect.
[0062] Preferably, the battery comprises a sodium ion battery.
[0063] The biomass-based hard carbon material provided by the present invention is more suitable for sodium ion batteries, and when used as a negative electrode active material, the performance improvement effect on the sodium ion battery is more excellent; however, in addition to sodium ion batteries, it is not ruled out that it can be used in other types of battery structures, such as lithium ion batteries, etc. In principle, the present invention is applicable to the uses of conventional hard carbon materials.
[0064] In addition, the sodium ion battery provided by the present invention, except for the relevant characteristics of the biomass-based hard carbon material defined above, the rest of the structure, preparation raw materials and preparation process are all conventional technical solutions. Those skilled in the art can make adaptive selections and adjustments based on actual needs, and the present invention will not elaborate on them.
[0065] Compared with the prior art, the present invention has the following beneficial effects:
[0066] The preparation method provided by the present invention coordinates various preparation processes and preparation sequences to regulate the raw material components of biomass carbon source, namely cellulose, hemicellulose and lignin, and the crystallinity of cellulose, thereby obtaining a biomass carbon source with high content and high crystallinity. The high-content crystalline cellulose can be converted into long graphite layers in the subsequent low-carbonization process, which surrounds and shrinks the active sites to form a closed-pore structure with a larger pore volume, thereby achieving the regulation of the pore structure of the hard carbon material obtained by carbonization, thereby achieving the purpose of improving the reversible sodium storage capacity and cyclic stability of the biomass-based hard carbon material. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] Figure 1 This is a flow chart of the preparation method provided in Example 1. DETAILED DESCRIPTION
[0068] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0069] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.
[0070] Example 1
[0071] This embodiment provides a biomass-based hard carbon material having a closed-pore structure inside. The preparation method of the biomass-based hard carbon material is as follows:
[0072] like Figure 1 As shown:
[0073] (1) drying and crushing the biomass carbon source rice husk to control its moisture content to 5% and the particle size to 30 mesh;
[0074] (2) treating the rice husk with a sodium hydroxide solution having a concentration of 3 mol / L for 4 h, wherein the mass ratio of the sodium hydroxide solution to the rice husk is 8:1, to obtain the rice husk treated with alkali;
[0075] (3) treating the alkali-treated rice husk with a 3 mol / L hydrochloric acid solution for 4 h, wherein the mass ratio of the hydrochloric acid solution to the rice husk treated in step (1) is 8:1, centrifuging the acid-treated material, washing with pure water until neutral, and then centrifuging and drying to obtain the acid-treated rice husk;
[0076] (4) placing the acid-treated rice husk in a high and low temperature oven, heating it to 140°C at a heating rate of 3°C / min, keeping it warm for 20 minutes, and then cooling it to room temperature at a cooling rate of 20°C / min to complete the crystallization pretreatment;
[0077] (5) heating the pre-crystallized material to 600° C. at a heating rate of 20° C. / min and keeping the temperature for 2 h to complete pre-carbonization, and crushing the pre-carbonized material so that the D50 particle size after crushing is 8 μm;
[0078] The crushed material is heated to 1500° C. at a heating rate of 5° C. / min for high-temperature carbonization and kept warm for 3 hours to obtain the biomass-based hard carbon material.
[0079] Example 2
[0080] This embodiment provides a biomass-based hard carbon material having a closed-pore structure inside. The preparation method of the biomass-based hard carbon material is as follows:
[0081] (1) drying and crushing the biomass carbon source rice husk to control its moisture content to 8% and a particle size of 50 mesh;
[0082] (2) treating the rice husk with a 5 mol / L sodium hydroxide solution for 1 h, wherein the mass ratio of the sodium hydroxide solution to the rice husk is 5:1, to obtain alkali-treated rice husk;
[0083] (3) treating the alkali-treated rice husk with a 5 mol / L hydrochloric acid solution for 1 h, wherein the mass ratio of the hydrochloric acid solution to the rice husk treated in step (1) is 5:1, centrifuging the acid-treated material, washing with pure water until neutral, and then centrifuging and drying to obtain the acid-treated rice husk;
[0084] (4) placing the acid-treated rice husk in a high and low temperature oven, heating it to 180°C at a heating rate of 1°C / min, keeping it at that temperature for 10 minutes, and then cooling it to room temperature at a cooling rate of 15°C / min to complete the crystallization pretreatment;
[0085] (5) heating the pre-crystallized material to 450°C at a heating rate of 15°C / min and keeping the temperature for 5 hours to complete pre-carbonization, and crushing the pre-carbonized material so that the D50 particle size after crushing is 10 μm;
[0086] The crushed material is heated to 1000° C. at a heating rate of 3° C. / min for high-temperature carbonization and kept warm for 5 hours to obtain the biomass-based hard carbon material.
[0087] Example 3
[0088] This embodiment provides a biomass-based hard carbon material having a closed-pore structure inside. The preparation method of the biomass-based hard carbon material is as follows:
[0089] (1) drying and crushing the biomass carbon source rice husk to control its moisture content to 10% and the particle size to 10 mesh;
[0090] (2) treating the rice husk with a sodium hydroxide solution having a concentration of 0.1 mol / L for 3 h, wherein the mass ratio of the sodium hydroxide solution to the rice husk is 10:1, to obtain the rice husk treated with alkali;
[0091] (3) treating the alkali-treated rice husk with a 0.1 mol / L hydrochloric acid solution for 3 h, wherein the mass ratio of the hydrochloric acid solution to the rice husk treated in step (1) is 10:1, centrifuging the acid-treated material, washing with pure water until neutral, and then centrifuging and drying to obtain the acid-treated rice husk;
[0092] (4) placing the acid-treated rice husk in a high and low temperature oven, heating it to 100°C at a heating rate of 2°C / min, keeping it warm for 30 minutes, and then cooling it to room temperature at a cooling rate of 17.5°C / min to complete the crystallization pretreatment;
[0093] (5) heating the pre-crystallized material to 500° C. at a heating rate of 17.5° C. / min and maintaining the temperature for 3 h to complete pre-carbonization, and crushing the pre-carbonized material to obtain a D50 particle size of 5 μm after crushing;
[0094] The crushed material is heated to 1300° C. at a heating rate of 4° C. / min for high-temperature carbonization and kept warm for 4 hours to obtain the biomass-based hard carbon material.
[0095] Example 4
[0096] The difference between this embodiment and embodiment 1 is that the biomass carbon source in this embodiment is bamboo; the alkaline substance in step (2) is ammonia water, and the acidic substance in step (3) is nitric acid.
[0097] The rest of the preparation methods and parameters were the same as those in Example 1.
[0098] Example 5
[0099] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, the concentration of the sodium hydroxide solution is 6 mol / L.
[0100] The rest of the preparation methods and parameters were the same as those in Example 1.
[0101] Example 6
[0102] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, the concentration of the hydrochloric acid solution is 6 mol / L.
[0103] The rest of the preparation methods and parameters were the same as those in Example 1.
[0104] Example 7
[0105] The difference between this embodiment and embodiment 1 is that in step (4) of this embodiment, the insulation temperature is 80°C.
[0106] The rest of the preparation methods and parameters were the same as those in Example 1.
[0107] Example 8
[0108] The difference between this embodiment and embodiment 1 is that in step (4) of this embodiment, the insulation temperature is 200°C.
[0109] The rest of the preparation methods and parameters were the same as those in Example 1.
[0110] Example 9
[0111] The difference between this embodiment and embodiment 1 is that in step (4) of this embodiment, the insulation time is 5 minutes.
[0112] The rest of the preparation methods and parameters were the same as those in Example 1.
[0113] Example 10
[0114] The difference between this embodiment and embodiment 1 is that in step (4) of this embodiment, after the heat preservation is completed, the temperature is naturally cooled to room temperature.
[0115] The rest of the preparation methods and parameters were the same as those in Example 1.
[0116] Comparative Example 1
[0117] The difference between this comparative example and Example 1 is that in this comparative example, the alkali treatment in step (2) is not performed.
[0118] The rest of the preparation methods and parameters were the same as those in Example 1.
[0119] Comparative Example 2
[0120] The difference between this comparative example and Example 1 is that in this comparative example, the acid treatment in step (3) is not performed.
[0121] The rest of the preparation methods and parameters were the same as those in Example 1.
[0122] Comparative Example 3
[0123] The difference between this comparative example and Example 1 is that in this comparative example, the crystallization pretreatment process of step (4) is not performed.
[0124] The rest of the preparation methods and parameters were the same as those in Example 1.
[0125] The pore structure of the biomass-based hard carbon materials obtained in Examples 1-10 and Comparative Examples 1-3 was characterized by closed pore volume and closed pore diameter using a gas adsorption method. The specific test conditions were: the hard carbon negative electrode material was placed at 150°C-300°C and a pressure of <10 -6 Bar environment for 1h-6h; then nitrogen is introduced at liquid nitrogen temperature to slowly return the pressure to normal pressure and then degas again for 10 -6 Bar, record the data to obtain the adsorption-desorption isotherm, and calculate the pore size distribution and pore volume data of the hard carbon negative electrode material according to the density functional theory (DFT) model. The test results are shown in Table 1.
[0126] Table 1
[0127] <![CDATA[Closed pore volume (cm 3 / g)]]> Average pore size (nm) Example 1 1.881 1.98 Example 2 1.860 1.94 Example 3 1.839 1.93 Example 4 1.803 1.90 Example 5 1.722 1.91 Example 6 1.663 1.82 Example 7 1.435 1.72 Example 8 1.512 1.79 Example 9 1.410 1.68 Example 10 1.642 1.81 Comparative Example 1 1.280 1.46 Comparative Example 2 0.886 1.03 Comparative Example 3 1.349 1.57
[0128] The biomass-based hard carbon materials provided in Examples 1-10 and Comparative Examples 1-3 were applied to batteries and performance tests were performed.
[0129] I. Battery Preparation:
[0130] Biomass-based hard carbon powder is mixed with conductive agent SuperP, adhesive sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 94.5:1.5:1.5:2.5, and a proper amount of water is added to form a slurry. The slurry is then evenly coated on the current collector copper foil. After drying, it is cut into a circular pole piece with a diameter of 18 mm. Under vacuum conditions, the pole piece is air-dried at 80°C for about 3 hours, vacuum-dried at 80°C for 6 hours, and rolled to a surface density of 4-7 mg / cm 2 The simulated battery was assembled in a glove box with an Ar atmosphere, using a metal sodium sheet as the counter electrode and 1 mol / L NaPF6 dissolved in ethylene carbonate solution as the electrolyte to form a CR2430 button battery.
[0131] II Performance Test
[0132] The prepared battery was subjected to electrochemical performance tests, specifically: a constant current charge and discharge mode was adopted, a charge and discharge test was carried out at a current density of 30 mA / g, and a battery cycle charge and discharge performance test was carried out under the conditions of a discharge cut-off voltage of 0 V and a charge cut-off voltage of 2.0 V; the test results are shown in Table 2.
[0133] Table 2
[0134]
[0135]
[0136] In summary, the preparation method provided by the present invention, the various preparation processes and the preparation sequence cooperate with each other, regulate the raw material components of biomass carbon source, cellulose, hemicellulose and lignin, and the crystallinity of cellulose, and obtain a biomass carbon source with high content and high crystallinity. The high-content crystalline cellulose can be converted into long graphite layers in the subsequent low-carbonization process, surrounding and shrinking the active sites to form a closed-pore structure with a larger pore volume, thereby realizing the regulation of the pore structure of the hard carbon material obtained by carbonization, and achieving the purpose of improving the reversible sodium storage capacity and cyclic stability of biomass-based hard carbon materials.
[0137] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a biomass-based hard carbon material, characterized in that: The preparation method comprises the following steps: The biomass carbon source is sequentially subjected to alkali treatment, acid treatment, crystallization pretreatment and carbonization to obtain the biomass-based hard carbon material.
2. The preparation method according to claim 1, characterized in that: The alkali treatment comprises: Mixing a biomass carbon source with an alkaline solution, performing an alkali treatment, and obtaining an alkali-treated product; Preferably, the concentration of the alkaline solution is 0.1 to 5 mol / L; Preferably, the mass ratio of the biomass carbon source to the alkaline solution is 1:(5-10); Preferably, the alkali treatment time is 1 to 4 hours; Preferably, the acid treatment comprises: The alkali-treated product is mixed with an acidic solution and subjected to acid treatment to obtain an acid-treated product; Preferably, the concentration of the acidic solution is 0.1 to 5 mol / L; Preferably, the mass ratio of the biomass carbon source to the acidic solution is 1:(5-10); Preferably, the acid treatment time is 1 to 4 hours.
3. The preparation method according to claim 1 or 2, characterized in that: The crystallization pretreatment comprises: The acid-treated product is subjected to low-temperature pretreatment.
4. The preparation method according to claim 3, characterized in that: The heating rate of the low temperature pretreatment is 1 to 3°C / min; Preferably, the insulation temperature after the low-temperature pretreatment is 100 to 180°C, and the insulation time after the low-temperature pretreatment is 10 to 30 minutes; Preferably, the cooling rate during the cooling process after the low-temperature pretreatment and heat preservation is 15-20°C / min.
5. The preparation method according to claim 1, characterized in that: The carbonization includes sequentially performing pre-carbonization and high-temperature carbonization.
6. The preparation method according to claim 5, characterized in that: The heating rate of the pre-carbonization is 15-20°C / min, the insulation temperature after the pre-carbonization heating is 450-600°C, and the insulation time after the pre-carbonization heating is 2-5h; Preferably, the pre-carbonized material is crushed to obtain a product with a median particle size D50 of 5 to 10 μm; Preferably, the heating rate of the high-temperature carbonization is 3-5°C / min, the insulation temperature after the high-temperature carbonization heating is 1000-1500°C, and the insulation time after the high-temperature carbonization heating is 3-5h.
7. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: Mixing a biomass carbon source with an alkaline solution having a concentration of 0.1 to 5 mol / L, and subjecting the mixture to an alkali treatment for 1 to 4 hours to obtain an alkali-treated product; The alkali-treated product is mixed with an acidic solution having a concentration of 0.1 to 5 mol / L, and subjected to acid treatment for 1 to 4 hours to obtain an acid-treated product; The product after the acid treatment is subjected to a crystallization pretreatment, the crystallization pretreatment comprising: heating to 100-180°C at a heating rate of 1-3°C / min, maintaining the temperature for 10-30min, and then cooling at a cooling rate of 15-20°C / min to obtain a substance after the crystallization pretreatment; Pre-carbonizing the pre-crystallized material at 450-600° C., crushing the pre-carbonized material, and carbonizing the crushed product at a high temperature of 1000-1500° C. to obtain the biomass-based hard carbon material; Wherein, the mass ratio of the biomass carbon source to the alkaline solution is 1:(5-10), and the mass ratio of the biomass carbon source to the acidic solution is 1:(5-10).
8. A biomass-based hard carbon material, characterized in that: The biomass-based hard carbon material is prepared by the preparation method according to any one of claims 1 to 7; The interior of the biomass-based hard carbon material has a closed-pore structure; Preferably, the pore volume of the closed-cell structure is 1.4 to 2.0 cm 3 / g, preferably 1.8 to 2.0 cm 3 / g.
9. A battery, characterized in that: The battery comprises the biomass-based hard carbon material as claimed in claim 8.
10. The battery according to claim 9, characterized in that The battery comprises a sodium ion battery.
Citation Information
Patent Citations
Hard carbon material for anode of sodium-ion battery, preparation method of hard carbon material and related sodium-ion battery
CN109678130A
Preparation method and application of biomass hard carbon negative electrode material of sodium-ion battery
CN116692858A
Bamboo-based hard carbon negative electrode material and preparation method and application thereof
CN118529710A
Bamboo-based and lignin-based hard carbon composite material, preparation method and application
CN118851151A
Biomass hard carbon negative electrode material and preparation method and application thereof
CN119118100A
Cited By
Biomass hard carbon and preparation method and application thereof
CN120664525B